2000
DOI: 10.1086/315513
|View full text |Cite
|
Sign up to set email alerts
|

Rhinoviruses Infect the Lower Airways

Abstract: Rhinoviruses are the major cause of the common cold and a trigger of acute asthma exacerbations. Whether these exacerbations result from direct infection of the lower airway or from indirect mechanisms consequent on infection of the upper airway alone is currently unknown. Lower respiratory infection was investigated in vitro by exposing primary human bronchial epithelial cells to rhinoviruses and in vivo after experimental upper respiratory infection of human volunteers. Bronchial infection was confirmed by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
383
0
27

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 509 publications
(434 citation statements)
references
References 46 publications
24
383
0
27
Order By: Relevance
“…Large community surveys, including the Virus Watch studies of the 1960-1970s (5), have shed light on some aspects of HRV biology and epidemiology. HRVs were also observed in LRTIs soon after their recognition (3), and data supporting a causative association have accumulated over the past decade (6,7). HRVs have also been implicated in exacerbations of asthma and chronic bronchitis and are increasingly reported in LRTIs of infants, elderly persons, and immunocompromised patients (4).…”
mentioning
confidence: 99%
“…Large community surveys, including the Virus Watch studies of the 1960-1970s (5), have shed light on some aspects of HRV biology and epidemiology. HRVs were also observed in LRTIs soon after their recognition (3), and data supporting a causative association have accumulated over the past decade (6,7). HRVs have also been implicated in exacerbations of asthma and chronic bronchitis and are increasingly reported in LRTIs of infants, elderly persons, and immunocompromised patients (4).…”
mentioning
confidence: 99%
“…Several studies attest to the ability of RV to infect the lower airways, supporting the notion of RV involvement in COPD exacerbations (9)(10)(11). RV readily infects airway epithelial cells from normal subjects in vitro, inducing the expression of such inflammatory mediators as IL-8, GRO-a, ENA-78, IL-6, and TNF-a (12)(13)(14)(15).…”
mentioning
confidence: 73%
“…11,[21][22][23] It is essential for understanding of physiopathological mechanisms of this disease to answer the question of whether RV can cause AB by establishing a lower airway infection or if it is associated with the condition by indirect mechanisms. Papadopoulos et al 13 demonstrated that RV is capable of causing lower airway infection in healthy adults and those with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10] Furthermore, upper airway infections by this virus have been associated with episodes of asthma exacerbation in older children and adults. [11][12] Nevertheless, Papadopoulos et al 13 demonstrated that RV may also cause lower airway infections. Previous studies have demonstrated an association between RV infection and wheezing in infants.…”
Section: Introductionmentioning
confidence: 99%